The The Relationship Between Socioeconomic Status and Access to Emergency Services for Catastrophic Diseases: The Relationship Between Socioeconomic Status and Access to Emergency Services for Catastrophic Diseases - REZA SYAHPUTRA, TENGKU MUHAMMAD (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Catastrophic illnesses are diseases that require immediate medical attention and often involve very high costs. Access to emergency services is a crucial factor in the management of these illnesses. Socioeconomic status (SES) is believed to have a significant impact on an individual's ability to access medical services. This study aims to analyze the relationship between socioeconomic status and access to emergency services for patients with catastrophic illnesses. The study uses a quantitative research design with a cross-sectional approach. The sample consists of 200 patients with catastrophic illnesses treated at referral hospitals. Data analysis was conducted using univariate descriptive statistics to describe respondent characteristics, and bivariate analysis using chi-square tests to examine the relationship between socioeconomic status and access to emergency services. The univariate analysis showed that the majority of respondents had low education, middle to lower income, and most worked in the informal sector. Approximately 65% of respondents reported difficulty accessing emergency services, particularly among the low socioeconomic group. The bivariate analysis revealed a significant relationship between socioeconomic status and access to emergency services (p < 0.05). Based on the findings, socioeconomic status significantly affects access to emergency services. Individuals with low socioeconomic status tend to face barriers in obtaining immediate medical care due to limited financial resources, knowledge, and access to adequate healthcare facilities. The conclusion of this study is that there is a significant relationship between socioeconomic status and access to emergency services for patients with catastrophic illnesses. Therefore, efforts to improve access and equitable distribution of emergency healthcare services, especially for people with low socioeconomic status, are necessary.